Molecular Identification of Strains of Caridean Species in a Tropical Lagoons of South-Western Nigeria - Akinwunmi, M. F.; Lawal-Are, A. O. (Journal of Scientific Research, 2019)
Species identification by morphological approach requires a high degree of experience, which is difficult and not practical enough for those interested in surveying a broad diversity of organisms. However, molecular or genetic approaches to identify species have been proposed and widely used by most scientists. DNA barcoding was used to identify Macrobrachium species occurring in three coastal lagoons (Badagry, Lagos and Epe) in South-western Nigeria. Samples of prawns for the DNA studies were collected from May to July 2015. The DNA of the Macrobrachium species was extracted using the phenol-chloroform protocol and Norgen tissue kit. Amplification and sequencing of the Macrobrachium species were carried out and further identification was done by comparing with sequenced data in the Genbank. New species of Macrobrachium were obtained in Badagry and Epe Lagoons having a close match with M. asperulum and M. nipponense at 85% and 84% respectively. M. asperulum and M. nipponense are reported in Badagry and Epe Lagoons for the first time.